Advances in computational intelligence systems : contributions presented at the 16th UK Workshop on Computational Intelligence, September 7-9, 2016, Lancaster, UK - Angelov, Plamen P.; Gegov, Alexander; Jayne, Chrisina; Shen, Qiang (Springer, 2016)
The book is a timely report on advanced methods and applications of computational intelligence systems. It covers a long list of interconnected research areas, such as fuzzy systems, neural networks, evolutionary computation, evolving systems and machine learning. The individual chapters are based on peer-reviewed contributions presented at the 16th Annual UK Workshop on Computational Intelligence, held on September 7-9, 2016, in Lancaster, UK. The book puts a special emphasis on novels methods and reports on their use in a wide range of applications areas, thus providing both academics and professionals with a comprehensive and timely overview of new trends in computational intelligence.
Keywords: Computational intelligence -- Congresses.; elektronické knihy; electronic books